Peranan Dewan Keamanan PBB Dalam Penyelesaian KonflikBersenjata Non-Internasional Di Libya - Ignesia Della Faragil; Levina Yustitianingtyas (Wijayakusuma Law Review, 2021)
AbstractThe United Nations or abbreviated to the UN is an international organization whose main objective is to maintainworld security and peace. In addition, the UN also aims to provide humanitarian assistance in times of famine,natural disasters and armed conflicts, both international and non-international conflicts. Like the conflict thatoccurred in the country of Libya in 2011, which was caused by the uncertainty of Libyan citizens against thegovernment led by Moammar Gaddafi. This conflict occurred involving two parties, namely between the ProKhadaffi and the Opposition. As a result of this conflict there were so many victims, which in the end this conflictled to a crime against humanity. In this case the United Nations through its Security Council immediately takesaction as an effort to maintain security and peace in the international world. This study aims to determine whatactions are being taken by the United Nations to resolve the conflict in Libya. This research is a normative legalresearch using the statue approach. The result of this research is that the UN Security Council issued Resolution1970 and Resolution 1973 which were concrete actions as an effort to resolve the conflict in Libya. The follow upof this conflict resolution was the issuance of Resolution 2009 by the UN Security Council.